Defining acute flares in knee osteoarthritis: a systematic review. Issue 7 (19th July 2018) - Parry, Emma L; Thomas, Martin J; Peat, George
Abstract : Objective: To identify and critically synthesise definitions of acute flares in knee osteoarthritis (OA) reported in the medical literature. Design: Systematic review and narrative synthesis. We searched Medline, EMBASE, Web of science and six other electronic databases (inception to July 2017) for original articles and conference abstracts reporting a definition of acute flare (or synonym) in humans with knee OA. There were no restrictions by language or study design (apart from iatrogenic-induced flare-ups, eg, injection-induced). Data extraction comprised: definition, pain scale used, flare duration or withdrawal period, associated symptoms, definition rationale, terminology (eg, exacerbation or flare), baseline OA severity, age, gender, sample size and study design. Results: Sixty-nine articles were included (46 flare design trials, 17 observational studies, 6 other designs; sample sizes: 15–6085). Domains used to define flares included: worsening of signs and symptoms (61 studies, 27 different measurement tools), specifically increased pain intensity; minimum pain threshold at baseline (44 studies); minimum duration (7 studies, range 8–48 hours); speed of onset (2 studies, defined as 'sudden' or 'quick'); requirement for increased medication (2 studies). No definitions included activity interference. Conclusions: The concept of OA flare appears in the medical literature but most often in the context of flare design trials (pain increases observed after stopping usual treatment). Key domains, used to define acute events in other chronic conditions, appear relevant to OA flare and could provide the basis for consensus on a single, agreed definition of 'naturally occurring' OA flares for research and clinical application. PROSPERO registration number: CRD42014010169.